Financial Health Analysis at Family Cooperative PGRI Uneversity Palembang - Desi Anggre Ani; Neta Dian Lestari; Chandra Kurniawan (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this study is to analyze financial health in family cooperatives pgri university Palembang. Design/methodology/approach: The method used in thisstudyis that of descriptive qualitative research. Data collection techniques consist of interviews, questionnaires, and documentation. Findings: The results of the Research assessment of family cooperative health of PGRI University Palembang in 2018, obtained a healthy predicate score of 85.05,a healthy predicate score of 80.05 in 2019, and a fairly healthy predicate score of 77.05 in 2020. Research limitations/ implications: This studyuses data on RAT financial statements in 2018-2020. Guided by the Regulation of The Deputy for Supervision of the Ministry of Cooperatives and SMEs of the Republic of Indonesia Number 06/Per/Dep. 6/IV/2016 on KSP and USP Health Assessment Guidelines usingaspects of cooperative health assessment which include capital aspects, aspects of productive asset quality,managementaspects,efficiency aspects, liquidity aspects, aspects of independence and cooperativeidentity, and aspects of cooperative identity. Practical implications:It is hoped that this research can provide benefits and information in the development of science and family cooperatives that could improve its financial health in the future. Originality/value:This paper is the result of the researcher’sanalysis to explore the level of the financial health of family cooperatives PGRI Palembang university Paper type: is categorized as a research paper.